Optimizing Democratic Learning: Exploring the Efficacy of Demonstrative Methods Among Middle School Students - Suyato Suyato; Yayuk Hidayah; Yayuk Ismiyani (PT. Anagata Sembagi Education, 2024)
This research aims to evaluate the effect of implementing the demonstration learning method on improving student learning outcomes in Pancasila and Citizenship Education (PPKn) learning in class VII of SMP Negeri 1 Yogyakarta. The demonstration learning method was chosen because it was considered to provide direct experience to students, increase understanding of concepts, and improve their practical skills in applying Civics values in everyday life. The research was conducted using a quantitative approach through a single group control pre-test post-test design. The sample for this research was class VII students of SMP Negeri 1 Yogyakarta who were divided into two groups, namely the experimental group who received learning using the demonstration method and the control group who received conventional learning. The research results show that the application of the demonstration learning method significantly improves student learning outcomes in Civics subjects. Data analysis showed that the average post-test score of the experimental group was significantly higher than the average post-test score of the control group. This indicates that the demonstration learning method is effective in increasing students' understanding of Civics material. The findings of this research provide important implications for educational practitioners to consider using demonstration learning methods in improving student learning outcomes, especially in Civics learning. Apart from that, this research also contributes to the development of learning theories and practices that are oriented towards student learning outcomes at the junior high school level.